Cathodic Protection of Copper Pipes Carrying Saline Water in the Presence of Aerobic Bacteria - S. Yaro, Aprael.; A.K.Rasheed, Hala; A.K. Rasheed, Haider (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Rates of zinc consumption during cathodic protection of a copper pipeline carrying saline water were measured by the loss in weight technique. The study of sacrificial anode cathodic protection of short copper tube using zinc strip extended axially in the pipe revealed that : (i) The increase of zinc consumption with time of exposure (1-3 h's) at different flow rates (turbulent flow) (300-600 l/hr) while the temperature , solution concentration and the pH were fixed at 20ºC, 3.5%wt NaCl, and pH=8 respectively in absence and presence of bacteria.(ii)Increase of zinc consumption with flow rates (300-600 l/hr) at different temperatures (10-40ºC) while solution concentration and time of exposure were fixed at 3.5 %wt NaCl and 3hr's respectively, in absence and presence of bacteria. (iii) Increase of zinc consumption with flow rates (300-600l/hr) at different solution concentrations (1-3.5 %wt NaCl) while the time of exposure and temperature were fixed at 3h's and 30ºC respectively in absence and presence of bacteria. Generally the Zn consumption during cathodic protection ranges from (2.424- 26.741 g/m2) and (5.352-27.296g/m2) in absence and presence of bacteria respectively.